2001
DOI: 10.1080/01421590120072187
|View full text |Cite
|
Sign up to set email alerts
|

The frequency selectivity of information-processing channels in the tactile sensory system

Abstract: The frequency selectivity of the P, NP I, and NP II channels of the four-channel model of mechanoreception for glabrous skin was measured psychophysically by an adaptation tuning curve procedure. The results substantially extend the frequency range over which the frequency selectivity of these channels is known and further confirm the hypothesis that the input stage of each of these channels consists of specific sensory nerve fibers and associated receptors. Specifically, the frequency characteristics of Pacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 47 publications
5
96
0
2
Order By: Relevance
“…The adapting vibration elevated detection thresholds by ϳ50% (t (8) ϭ 4.23; p Ͻ 0.001, comparing thresholds in the no-view condition against baseline thresholds measured without an adapting vibration), consistent with previous reports (Gescheider et al, 2001). The adapting vibration also lowered discrimination thresholds by ϳ25% (t (8) ϭ 2.47; p ϭ 0.039), an effect that has been reported for discrimination of vibration frequency (Tommerdahl et al, 2005) but not, to our knowledge, for amplitude.…”
Section: Experiments 1-4supporting
confidence: 89%
“…The adapting vibration elevated detection thresholds by ϳ50% (t (8) ϭ 4.23; p Ͻ 0.001, comparing thresholds in the no-view condition against baseline thresholds measured without an adapting vibration), consistent with previous reports (Gescheider et al, 2001). The adapting vibration also lowered discrimination thresholds by ϳ25% (t (8) ϭ 2.47; p ϭ 0.039), an effect that has been reported for discrimination of vibration frequency (Tommerdahl et al, 2005) but not, to our knowledge, for amplitude.…”
Section: Experiments 1-4supporting
confidence: 89%
“…40, 5, p. 817-825. Another approach to identifying tactile channels responsible for perception thresholds is to determine a slope that represents the frequency-dependence of the perception threshold expressed in terms of the vibration displacement. The slope of the displacement threshold of the Pacinian receptors between 15 and 200 Hz has been suggested to be approximately -12 dB per octave (e.g., Verrillo, 1963;Gescheider, 1976;Verrillo and Gescheider, 1977;Bolanowski et al, 1988;Gescheider et al, 2001). When the present thresholds are expressed in terms of displacement (see and 35 Hz (Bolanowski et al 1988;Gescheider et al, 2001;, while the Ruffini endings (NP II) respond with a slope of -5.0 to -6.0 dB per octave between about 15 and 250 Hz (Capraro et al, 1979;Gescheider et al, 1985;Bolanowski et al, 1988).…”
Section: Effect Of Frequencymentioning
confidence: 99%
“…The slope of the displacement threshold of the Pacinian receptors between 15 and 200 Hz has been suggested to be approximately -12 dB per octave (e.g., Verrillo, 1963;Gescheider, 1976;Verrillo and Gescheider, 1977;Bolanowski et al, 1988;Gescheider et al, 2001). When the present thresholds are expressed in terms of displacement (see and 35 Hz (Bolanowski et al 1988;Gescheider et al, 2001;, while the Ruffini endings (NP II) respond with a slope of -5.0 to -6.0 dB per octave between about 15 and 250 Hz (Capraro et al, 1979;Gescheider et al, 1985;Bolanowski et al, 1988). For both the UPPER and the LOWER hand positions in the current study, the slope of the thresholds at frequencies less than 16 Hz were about half the slope expected for the Pacinian channel but typical of the slope of the NP I and NP II channels.…”
Section: Effect Of Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…FA I, SAI and SA II fibres, respectively), some of which seem incapable of temporal or spatial summation and whose responses depend on stimulus gradients (Gescheider [7]; Verrillo [8]). Later studies by Bolanowski et al [13] and Gescheider et al [14] demonstrated a fourchannel model of vibrotactile perception by determining threshold responses of three tactile channels within the non-Pacinian system (NP I, NP II, and NP III channels corresponding to FA I, SA II and SA I fibres, respectively) in the glabrous skin of the hand.…”
mentioning
confidence: 99%